Safety Belt Product Quality Analysis to Analyze The Number of Defects Using The Seven Tools Method at PT. XYZ - Aldino Rafly Rahma Dana; Donoriyanto, Dwi.Sukma (AI Society & STMIK Indonesia, 2024)
PT XYZ is a company that operates in the automotive spare parts sector. The problem at PT XYZ is quality defects in safety belt part products. Based on these problems, its necessary to carry out an analysis of improvements in production so that it can produce quality products and reduce product defects.Seven tools are seven basic tools used to solve problems faced by production, especially problems related to quality. Quality improvement using seven tools can explain in detail the types of product defects and the causes of these product defects [5]Based on the data analysis that has been carried out, improvements are proposed to improve product quality, Get used to working accordingly SOP, Provide a place to products in a safe place, Familiarize workers to carry out periodic checks, Streamlining air circulation by creating vents, The head production provides a closed storage area, Instruct material suppliers to provide anti-rust coatingsBased on the data analysis that has been carried out, improvements are proposed to improve product quality, Get used to working accordingly SOP, Provide a place to products in a safe place, Familiarize workers to carry out periodic checks, Streamlining air circulation by creating vents, The head production provides a closed storage area, Instruct material suppliers to provide anti-rust coatings